Emotional Trajectory at Different Career Stages: Two Excellent Teachers’ Stories - Chen, Junjun; Lee, John Chi-Kin; Dong, Jihe (Frontiers in Psychology, 2020)
The current study aimed to investigate excellent teachers’ emotional journey, particularly, the trajectory of emotional experiences and emotional labor strategies at different career phases. The research used a case-study approach to explore the storied experience of two teachers (female and male) who were bestowed the Provincial Excellent Teacher Award. They were close to retirement so they could retrieve emotional experiences from across their entire career. Individual semi-structured interviews were utilized as a major data source, supplemented with relevant documentation and phone calls to achieve data triangulation. Thematic analysis was adopted to deal with data. The findings demonstrated a dynamic pattern of emotions and emotional labor, transiting from one teacher career stage to another. It was observed that the female teacher experienced mixed emotions but the male teacher had more negative emotions at the early stage. Both teachers claimed more positive emotions in the middle stage and a high level of satisfaction in the late stage. Both of them employed genuine expression and surface acting strategies in the first two stages. In the late stage, the female teacher used a combination of genuine expression and deep acting with more empathy, whilst the male teacher adopted a combination of surface acting and genuine expression aiming for a neutral atmosphere. Social values, organizational demands professional self, and gender are discussed for possibly resulting in these discrepancies.